2013
DOI: 10.1007/s11255-012-0367-x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K status in chronic kidney disease: a report of a study and a mini-review

Abstract: Hepatic vitamin K-dependent proteins (e.g., Factors II, VII, IX and X) form part of the clotting cascade. Factor II (FII)/Prothrombin incorporates 10 Glu residues on the N-terminal region that are γ-carboxylated to Gla residues by the action of γ-glutamyl carboxylase to confer biological activity. Vitamin K is also required for the normal function of Matrix Gla Protein (MGP)--one of several non-clotting-related extra-hepatic vitamin K-dependent proteins. MGP is known to have protective action against vascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 22 publications
0
18
1
Order By: Relevance
“…This was not the case in our population (data not shown) but our sample of prevalent VKA treated patients (n = 23) was probably too small. Several authors have suggested that VKA treatment is a risk factor for vascular calcifications or calciphylaxis in HD patients but this assertion deserves further study [24, 32, 35, 39–46]. Third, the Kauppila method is not the most sensitive way of detecting vascular calcifications and we did not directly measure neither vitamin K levels nor other vitamin K dependent protein like PIVKA-II (protein induced by vitamin K absence II).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…This was not the case in our population (data not shown) but our sample of prevalent VKA treated patients (n = 23) was probably too small. Several authors have suggested that VKA treatment is a risk factor for vascular calcifications or calciphylaxis in HD patients but this assertion deserves further study [24, 32, 35, 39–46]. Third, the Kauppila method is not the most sensitive way of detecting vascular calcifications and we did not directly measure neither vitamin K levels nor other vitamin K dependent protein like PIVKA-II (protein induced by vitamin K absence II).…”
Section: Discussionmentioning
confidence: 87%
“…This high concentration of dp-ucMGP in HD patients is not fully understood. These patients are clearly sensitive to vitamin K deficiency, and this is likely because the recommended diet in HD patients is deficient in vitamin K [1922, 24]. However, decreased excretion or catabolism of MGP associated with decreased glomerular filtration is also a plausible explanation for the molecular weight of MGP (11 kDa) [7, 33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is why currently, the most reliable markers of vitamin K status are considered circulating dp-ucMGP and proteins induced by vitamin K absence or antagonism (PIVKA), which is a collective marker of all undercarboxylated, inactive vitamin K dependent proteins [ 53 ]. The prevalence of vitamin K deficiency (measured by PIVKA) augments in parallel with progression of CKD [ 54 ] and reaches 83–97% in HD patients [ 35 , 55 ]. Moreover, in these populations, subclinical vitamin K deficiency (assessed either by PIVKA or dp-ucMGP) has been repeatedly associated with increased VC and CV disease [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by the influence of decreased kidney function on the carboxylation of matrix Gla-protein, another vitamin K-dependent protein. 4446 The slower rate of INR decline, together with other factors (e.g. uremia, platelet dysfunction) known to be associated with kidney disease, could explain the higher risk of hemorrhagic complications.…”
Section: Discussionmentioning
confidence: 99%